Evaluation of Child Development Centre Based Intervention for Children with Multiple Disability (Journal of National Institute of Neurosciences Bangladesh, 2021)
Background: Children with multiple disabilities usually have more than one significant disability that may include speech, physical mobility, learning, mental retardation, visual, hearing, and possibly others.Objective: The purpose of the present study was to evaluate the types of multiple disabilities in children with cerebral palsy and epilepsy and their fate after the intervention.Methodology: This retrospective observational study was conducted at Dhaka Shishu hospital from January 2011 to Decemberb2011.Children with multiple disabilities were referred to the child development center of Dhaka Shishu Hospital and were assessed for impairments and appropriate intervention done in special clinics.Result: Out of 540 children 66% were male. 43% of children were age group from 12-23 months. 58% had tetraplegic cerebral palsy (CP) with epilepsy and the second-highest group was diplegic CP with epilepsy 75(14.0%). Among 72 selected children who came in regular follow up, all children had motor disabilities. Cognitive delay, speech delay, vision and hearing impairment were found in 50%, 79%, 58% and 54% respectively. After intervention more improvement was found in motor function (92%).Conclusion: Intervention in specialized clinics improved the quality of life of children with multiple disability.Journal of National Institute of Neurosciences Bangladesh, January 2021, Vol. 7, No. 1, pp. 38-41